Are global spillovers complementary or competitive? Need for international policy coordination. (February 2021) - Bhattarai, Keshab; Mallick, Sushanta K.; Yang, Bo
Highlights: We estimate structural DSGE and VAR models comprising an emerging and a developed economy. We examine the interdependence and spillover effects of technology and macroeconomic policy shocks. The UIP risk premium channels the transmission of spillovers between these two economies. This paper finds complementarity of technological innovations and competitiveness of monetary policy shocks. Competitive responses reflect limited international integration of emerging markets, requiring policy coordination. Abstract: Advanced and emerging economies are becoming more interdependent with rapid pace of globalization of capital markets and technological innovations in recent years. We examine whether technology and monetary policy shocks get transmitted between advanced and emerging market economies and to what extent they generate complementary or competitive effects. Given the globally integrated nature of capital markets, we uncover a transmission mechanism by which technology and policy shocks in advanced and emerging countries spill over between them through the capital flow channel. We mainly investigate whether analysis from a SVAR model by econometricians provides empirically similar conclusions to those from a macroeconomic theory-based DSGE model in measuring the impact of demand-side policy and technology shocks. We fit our VAR models to the same time series data used to calibrate and estimate the DSGE model. We conclude that monetary and fiscal policy shocks are competitive between the US (advanced economy) and India (emerging market), while domestic and global technology shocks or the exchange rate shocks have complementary effects. Intuitively, technology enhances productivity in both countries, while policy shocks tend to drive capital to a country with higher rate of return. Thus policy shocks in advanced countries could have unintended effects in terms of capital inflows to emerging economies and hence greater coordination of policies can help limit adverse cross-border spillovers.